Leadership in the library and information science professions: - Winston, Mark D. (Haworth Information Press, 2001)
Leadership in the Library and Information Science Professions offers fresh ideas for developing and using leadership skills, including: ecruiting tips for identifying potential leaders; staff training and development ; restructuring the organization to encourage full staff participation; budget strategies for successful leaders; issues of gender and ethnic diversity; evaluating and assessing leadership